Analysis of MADS-Box Gene Family Reveals Conservation in Floral Organ ABCDE Model of Moso Bamboo (Phyllostachys edulis) - Cheng, Zhanchao; Ge, Wei; Li, Long; Hou, Dan; Ma, Yanjun; Liu, Jun; Bai, Qingsong; Li, Xueping; Mu, Shaohua; Gao, Jian (Frontiers in Plant Science, 2017)
MADS-box genes are transcription factors which play fundamental roles in flower development and regulation of floral organ identity. However, till date, identification and functions of MADS-box genes remain largely unclear in Phyllostachys edulis. In view of this, we performed a whole-genome survey and identified 34 MADS-box genes in P. edulis, and based on phylogeny, they were classified as MIKCC, MIKC*, Mα and Mβ. The detailed analysis about gene structure and motifs, phylogenetic classification, comparison of gene divergence and duplication are provided. Interestingly, expression patterns for most genes were found similar to those of Arabidopsis and rice, indicating that the well-established ABCDE model can be applied to P. edulis. Moreover, we overexpressed PheMADS15, an AP1-like gene, in Arabidopsis, and found that the transgenic plants have early flowering phenotype, suggesting that PheMADS15 might be a regulator of flowering transition in P. edulis. Taken together, this study provides not only insightful comprehension but also useful information for understanding the functions of MADS-box genes in P. edulis.